UJI ORGANOLEPTIK TELUR ASIN DENGAN PENAMBAHAN SARI JAHE - Mohamad Irvan Zhuhri; Resti Yuliana; Edya Moelia Moeis (Universitas Islam Balitar, 2021)
The purpose of the research was to determine the effect of adding ginger extract on organoleptic test of salted egg. The research method used a completely randomized design (CRD). The treatment in this research was the addition of ginger extract with 4 treatments, the addition of 0 grams, 200 grams, 400 grams and 600 grams of ginger extract. This research was carried out in the Laboratory of the Animal Husbandry Faculty, Islamic Balitar University, Blitar since August 25th until September 6th, 2021. The result showed that there was a significant effect between the addition of ginger extract to salted egg. The best treatment for white and yolk eggs was P0 treatment (no addition of ginger extract). The scent in the P3 treatment (addition of 600 grams of ginger extract) is quite typical of ginger scent. The texture of the egg whites in treatment P1 (addition of 200 grams of ginger extract) is quite springy, the texture of the egg yolks in treatment P3 (addition of 600 grams of ginger extract) is quite gritty. The taste in the P3 treatment (addition of 600 grams of ginger extract) is quite ginger taste.